Indian Ocean Trade in Antiquity, The : Political, Cultural, and Economic Impacts (Routledge, 2018)
"The period from the death of Alexander the Great to the rise of the Islam (c. late fourth century BCE to seventh century CE) saw a significant growth in economic, diplomatic and cultural exchange between various civilisations in Africa, Europe and Asia. This was in large part thanks to the Indian Ocean trade. Peoples living in the Roman Empire, Parthia, India, and Southeast Asia increasing had access to exotic foreign products, while the lands from which they derived, and the peoples inhabiting these lands, also captured the imagination, finding expression in a number of literary and poetic works. This book provides a range of chapters that explore the economic, political and cultural impact of this trade on these diverse societies, written by international experts working in the fields of Classics, Archaeology, South Asian studies, Near Eastern studies and Art History. The three major themes of the book are the development of this trade, how consumption and exchange impacted on societal developments, and how the Indian Ocean trade influenced the literary creations of Graeco-Roman and Indian authors. Academics, students, and those with a general interest in world history alike should find this book of interest. In particular, those whose research focuses on antiquity, as well as scholars working on later periods of Indian Ocean history, will find this work a valuable resource"--